1992
DOI: 10.1002/jcb.240500311
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoproteins derived from subnuclear RNA polymerase complexes of metastatic large‐cell lymphoma cells possess transcription activities and regulatory properties in vitro

Abstract: Intact nuclei derived from poorly or highly liver-metastatic murine large-cell lymphoma cell line RAW117 were digested to discrete subchromatin deoxyribonucleoprotein/ribonucleoprotein (DNP/RNP) complexes with Msp-I. The DNP/RNP complexes were composed of DNP/RNPs which were derived from the DNP/RNP complexes by incubation in the presence or absence of DNase-I and subsequent isolation by two-dimensional [isoelectric focusing/sodium dodecylsulfate (SDS)] polyacrylamide gel electrophoresis (PAGE), electroelution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
1999
1999

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…NPGT has been used to analyze NPC fractions from various cell systems for the presence of specific genes as well as enzymatic activity. For example, we have screened NPC from metastatic variants of the murine large cell lymphoma for the presence of abl, p53, c-neu, c-H-ras, ␤-casein, 18S rDNA, and µ-chain immunoglobulin genes and found that these genes were differentially expressed in the highly metastatic variants [Rosenberg-Nicolson and Nicolson 1992b;Nicolson and Nicolson, 1992b, 1993,1994aNicolson et al, 1995;1996]. We also used RNA back-hybridization assays to determine whether individual nuclei-derived NPC are capable of synthesizing mRNA in vitro that could back-hybridize to specific genes, indicating the presence of enzymatic activities capable of producing RNA with specific sequences capable of hybridizing back to the gene sequences from which they were derived.…”
Section: Discussionmentioning
confidence: 99%
“…NPGT has been used to analyze NPC fractions from various cell systems for the presence of specific genes as well as enzymatic activity. For example, we have screened NPC from metastatic variants of the murine large cell lymphoma for the presence of abl, p53, c-neu, c-H-ras, ␤-casein, 18S rDNA, and µ-chain immunoglobulin genes and found that these genes were differentially expressed in the highly metastatic variants [Rosenberg-Nicolson and Nicolson 1992b;Nicolson and Nicolson, 1992b, 1993,1994aNicolson et al, 1995;1996]. We also used RNA back-hybridization assays to determine whether individual nuclei-derived NPC are capable of synthesizing mRNA in vitro that could back-hybridize to specific genes, indicating the presence of enzymatic activities capable of producing RNA with specific sequences capable of hybridizing back to the gene sequences from which they were derived.…”
Section: Discussionmentioning
confidence: 99%